Analisis Metode Bermain Peran Terhadap Kemampuan Sosial Pada Anak Usia 4-6 Tahun di Tk Beringin Permai - Meriati Tumangger; Winarti Agustina; Julita Herawati P (Institut Nalanda, 2023)
The aim of this research is to determine the percentage of Role Playing Methods on Social Skills in Children Aged 4-6 Years at Beringin Permai Kindergarten. The method used in this research is a quantitative research method with descriptive statistics. The population is all children aged 4-6 years in Beringi Permai Kindergarten, totaling 15 people, and the sampling technique, namely saturated sampling, is that all members of the population are used as samples, namely 15 people. Data collection techniques were carried out using observation sheets and documentation. Based on the results of the recapitulation of Social Capability data, there were 6.7% in the MB category, 20.0% in the BSH category, and 73.3% in the BSB category. Furthermore, based on the t test, the value of tcount > ttable (29.588 > 1.761) was obtained. then it can be concluded that H0 is rejected and Ha is accepted, namely the Analysis of Role Playing Methods on Social Abilities in Children Aged 4-6 Years at Beringin Permai Kindergarten is >50% of what is expected to be accepted